2003
DOI: 10.1046/j.1528-1157.2003.55302.x
|View full text |Cite
|
Sign up to set email alerts
|

Cysticercosis as a Major Risk Factor for Epilepsy in Burundi, East Africa

Abstract: Summary:  Purpose: Human cysticercosis is a direct consequence of infection by Taenia solium larvae (Cysticercus cellulosae). Results of studies on the impact of neurocysticercosis on epilepsy in Africa are inconsistent. The objective was to evaluate the role of cysticercosis in epilepsy in Burundi. Methods: A prevalent matched case–control design was used in the Kiremba area, Burundi, between March and April 2001. One case with epilepsy was matched to two control subjects, according to their age. Cases were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
71
4
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 20 publications
8
71
4
1
Order By: Relevance
“…On the other hand, the observed prevalence is significantly less to that reported byNsengunya et al [30] which was 31.5% (n = 648) of the health individuals positive to anticysticercal antibodies in Burundi. The human cysticercosis prevalence reported by this study had the highest frequency in ages between 16 -45 years.…”
Section: Discussioncontrasting
confidence: 77%
“…On the other hand, the observed prevalence is significantly less to that reported byNsengunya et al [30] which was 31.5% (n = 648) of the health individuals positive to anticysticercal antibodies in Burundi. The human cysticercosis prevalence reported by this study had the highest frequency in ages between 16 -45 years.…”
Section: Discussioncontrasting
confidence: 77%
“…This study is an extension of the matched case-control study for epilepsy carried out by Nsengiyumva et al (2003), which found a statistically significant association between the presence of antibodies against T. solium cysticerci and epilepsy. This association persisted after correcting for other factors potentially responsible for epilepsy.…”
Section: Discussionmentioning
confidence: 89%
“…This association persisted after correcting for other factors potentially responsible for epilepsy. In this study, 303 out of 324 sera from epileptic patients as well as 606 from the 648 sera from control persons originally tested by Nsengiyumva et al (2003) were equally tested by the Ag-ELISA. Significantly more (38.3%) people with epilepsy were positive in the Ag-ELISA than controls (20.0%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An unknown number of human zoonotic infections go undiagnosed, unrecorded, and thus untreated because of poor knowledge of easy-to-use diagnostic and screening tests. For example, recent studies have indicated that 30% to 50% of cases of epilepsy in endemic countries are associated with neurocysticercosis [24]. Many zoonoses cause febrile symptoms, but in sub-Saharan Africa clinicians often ascribe fever to malaria, although an estimated 50% to 80% of fevers in Africa are misdiagnosed as malaria [25].…”
Section: S349mentioning
confidence: 99%